Etika Pemimpin Penerbangan: Pelatihan, Perilaku Etis, dan Dampaknya Terhadap Kinerja Tim - Angga Budiman Ardiwisastra; Supardam, Dhian (Jurnal Bisnis dan Operasi Penerbangan, 2024)
This systematic literature review investigates the relationship between aviation leader ethics, training programs, and their impact on team performance. The study synthesizes existing research on ethical leadership behaviors, training interventions, and team outcomes in the aviation sector. The findings highlight the importance of specialized ethics training in enhancing ethical behavior among aviation leaders, which in turn positively affects team performance. Specifically, the review emphasizes the role of ethical decision-making frameworks, such as the Four-Way Test and the PLUS Model, in fostering a culture of ethical awareness, responsibility, and accountability among aviation professionals. Additionally, the study underscores the significance of implementing and evaluating ethics training programs effectively in aviation organizations, considering factors such as the ethical issues and risks relevant to the organization, the learning objectives and outcomes of the training program, and the alignment of the program with the organization's mission, vision, values, and strategic objectives. The review concludes that prioritizing the development of an ethical culture and ethics training is crucial for enhancing team performance and operational safety in the aviation sector.